Harmoni Fungsi dan Estetika: Studi Tentang Pengaruh Kolom Utama dan Kolom Praktis Terhadap Desain Bangunan Gedung - Reny Kartika Sary; Meldo Andi Jaya; Randy Rizal (Universitas Muhammadiyah Palembang, 2024)
Columns are components or parts of a building that function as the main structure of the building. In some cases, building columns have also developed an aesthetic function that displays artistic value on the facade. Therefore, proper and thorough planning of the columns will highlight the unique character of the building. The aim of this research is to evaluate the effectiveness of main columns and practical columns as structural and aesthetic elements in building design. The emphasis on the importance of column aesthetics is the novelty of this research. The research method used is a qualitative descriptive method using a theoretical approach, a literature study, and field observation. The conclusion results show that building forming factors are elements that link the value of the shape and structure of the columns so that they become their own visual attraction. Therefore, architects must be careful when considering these elements to create synergy and harmony between structure and architecture.